2008
DOI: 10.1002/jssc.200700455
|View full text |Cite
|
Sign up to set email alerts
|

Study of pepsin phosphorylation using immobilized metal affinity chromatography

Abstract: The interactions of pepsin with immobilized trivalent metal ions and the participation of the enzyme phosphate group in this process were investigated using high performance immobilized metal affinity chromatography. Two different sorbents were used: the newly prepared one, consisting of Ga(3+ )chelate of (6-amino-1-hydroxyhexane-1,1-diyl) bis(phosphonic acid) covalently bound to a methacrylate support (BP-Ga(3+)), and the commercial one, containing immobilized Fe(3+ )ions (POROS MC20-Fe(3+)). The comparison o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In another study, a comparison was made between Poros-Fe 3+ IMAC column and metal oxide affinity chromatography with TiO 2 (titanium dioxide)-based methods using simple and complex mixture of peptides where they observed that although usage of low pH loading buffer can increase enrichment selectivity, but it also results in low recovery of phosphopeptides [32,33]. The technique was used to separate and enrich phosphoproteins from an epidermal growth factor-stimulated human epidermoid carcinoma A431 cell lysate [31].…”
Section: Resultsmentioning
confidence: 99%
“…In another study, a comparison was made between Poros-Fe 3+ IMAC column and metal oxide affinity chromatography with TiO 2 (titanium dioxide)-based methods using simple and complex mixture of peptides where they observed that although usage of low pH loading buffer can increase enrichment selectivity, but it also results in low recovery of phosphopeptides [32,33]. The technique was used to separate and enrich phosphoproteins from an epidermal growth factor-stimulated human epidermoid carcinoma A431 cell lysate [31].…”
Section: Resultsmentioning
confidence: 99%
“…Purification procedures based on the use of affinity tags are well developed to enable different proteins to be purified using some common methods. Among those affinity tags, short histidine stretches or His‐tags typically fused to the C‐ or N‐terminus, enables the purification of these recombinant proteins from the crude extracts of the host cells by a single step, i.e., immobilized metal ion affinity chromatography . More than 50% of the recombinant proteins expressed in prokaryotic host cell are purified by immobilized metal ion affinity chromatography and its future outlook is very bright indeed for many purification processes such as interferon, nucleoside diphosphatase, trypsin inhibitors, glycogen phosphorylase and lactate dehydrogenase (LDH) .…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of MS and MS‐based phosphopeptide enrichment techniques, such as with TiO 2 and immobilized metal affinity chromatography (IMAC), high‐throughput phosphoproteomic analysis in human and animal disease phosphoproteomic studies has progressed rapidly . Among the various phosphopeptide purification methods, IMAC is fast, easy‐to‐modify, and economic for the enrichment of phosphopeptides prior to MS analysis . IMAC has been proved as a powerful method for the selective enrichment of phosphopeptides from animal organs, tissues, and model plants .…”
Section: Introductionmentioning
confidence: 99%